2007
DOI: 10.3171/spi.2007.6.2.141
|View full text |Cite
|
Sign up to set email alerts
|

The effects of magnesium particles in posterolateral spinal fusion: an experimental in vivo study in a sheep model

Abstract: Object Magnesium has recently become a material of interest as a biocompatible and biodegradable implant metal. Authors of several reports have noted the potential bone-cell activating or bone-healing effect of high Mg ion concentrations. The classic method for achieving intertransverse process fusion involves using an autologous iliac crest bone graft. Several studies have been performed to investigate enhancement of this type of autograft fusion. To the authors’ kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 36 publications
1
16
0
2
Order By: Relevance
“…This is the first study of CoCr-alloy-induced effects in the peri-spine region [6]. However, our results are consistent with past investigation of peri-spine implant debris such as magnesium particles [22], titanium particles [7] and PEEK particles [30,36]. These past in vivo investigations of spinal implant particles demonstrated that clinically relevant particles elicit chronic mild inflammatory reactions [5,7,17,29,30].…”
Section: Discussionsupporting
confidence: 80%
“…This is the first study of CoCr-alloy-induced effects in the peri-spine region [6]. However, our results are consistent with past investigation of peri-spine implant debris such as magnesium particles [22], titanium particles [7] and PEEK particles [30,36]. These past in vivo investigations of spinal implant particles demonstrated that clinically relevant particles elicit chronic mild inflammatory reactions [5,7,17,29,30].…”
Section: Discussionsupporting
confidence: 80%
“…6) Five studies (58 levels) reported fusion imaging scores for instrumented lumbar PLF using iliac crest autograft [16][17][18][19][20]. Imaging fusion results were high by 16 weeks postoperative and approached bilateral fusion at 24 weeks postoperative.…”
Section: Lumbar Plfmentioning
confidence: 99%
“…Imaging fusion results were high by 16 weeks postoperative and approached bilateral fusion at 24 weeks postoperative. However, one study at 24 weeks postoperative had a lower fusion score; this study differed in that instrumentation was only placed unilaterally [18]. This study also used histology to assess fusion at 24 weeks postoperative, and again resulted in a lower score than the average seen on imaging [18].…”
Section: Lumbar Plfmentioning
confidence: 99%
“…Bu özellikleri Mg alaşımlarını otomotiv, bilgisayar, havacılık, mobil telefonlar, spor malzemeleri gibi pek çok endüstride değerli kılmaktadır. Düşük ağırlık ve metabolizmaya uyumu açısından implant malzemesi olarak da kullanılmaktadır [11][12][13][14][15][16]. Ayrıca son yıllarda enerji kaynaklarını daha verimli kullanmak için yapılan çalışmalara hız verilmiştir.…”
Section: Gđrđşunclassified